Investigating the predictive role of psychological factors in the incidence of sports injuries (musculoskeletal) of elite male volleyball players - Alireza kazeminasab; Reza Aminzadeh; Nasser Mohammad Rahimi (Sport Sciences and Health Research)
Introduction: This study aimed to investigate the predictive role of psychological factors in the incidence of sports injuries (musculoskeletal) of elite male volleyball players.Martials and Methods: This was a descriptive-correlational research study design. The study was conducted with 150 elite male volleyball players in the Premier League of Khorasan Razavi province in 2020. In order to collect data, three standard questionnaires including Sports Injuries Questionnaire (Esmaeili, 2014), Personality Traits Questionnaire [18], and Competitive State Anxiety Questionnaire (CSAI-2) Rainer and Martens (1990) were used. In order to analyze the data in this study, SPSS software version 23 was used.Results: The results show that competitive anxiety can explain sports injuries (musculoskeletal) in the first model. In the second model, when the somatic anxiety variable is added, competitive anxiety and somatic anxiety variables can explain sports injuries. In the final model, the factors of competitive anxiety, somatic anxiety, self-confidence, risk-taking, excitement, and aggression can explain sports injuries.Conclusion: It can be said that psychological factors play a role in the incidence of sports injuries (skeletal-muscular) of elite male volleyball players.